Tinjauan Ekohidraulik Pada Uji Model Fisik Bangunan Pelimpah Waduk Pidekso Kabupaten Wonogiri - Suprijanto, Heri; Masrevaniah, Aniek; Prasetijo, Hari; Sisinggih, Dian; Primantyo, Andre (Fakultas Teknik, Universitas Brawijaya, 2013)
Within this physical hydraulic model of spillway of the Pidekso Dam, the experiment consisted of 9-series of testing; 4-series were testing of narrowing the angle of transition channel by 24 degree while 5others were by 12 degree. For the testing of series No.0 (original design) to No.8, the flow capacity was adequate for various discharges over spillway and outlet structure. Overall, the best hydraulic performance of the model was achieved by series No.4 in term of flow condition (uniformly distributed). This was a model of transition channel with angle of transition of 12 degree and no baffle apron used.Basically, all of testing of the model series No.0 to No.8 brought the positive impact to the downstream-part (section No.36) by considering the dissolved oxygen (DO) level. It was ranging from 11.1 mg/l to 14.2 mg/ l. According to the results of DO level, then only the series No.0 to No.3 were chosen as alternatives design for the case of transition channel with the angle of 24 degree combined with various dimensions of baffle apron. There were regular changes of DO level but the values were still lying above the minimum requirement level and were not harmful for fishery.By respecting to the eco-hydraulic concept, the downstream waterway was designed to be the stone pitching combined with vegetation. It was suggested that the bare floodplain at downstream-part need to be greening by mean of vegetation.Keyword: dam, spillway, baffle apron, dissolved oxygen